The Collaboration Management and Employee Views of Work and Skills in Services for Children and Families in Finnish Municipalities: The Collaboration Management and Employee Views of Work and Skills - Kanste, Outi; Halme, Nina; Perälä, Marja-Leena (Nordic Journal of Working Life Studies, 2016)
The study explored how collaboration management is connected with employee views of work and skills in the health care, social welfare, and education sectors that provide services for children and families in municipalities. Collaboration management in children and family services involves increasing awareness of services, organizing agreed collaboration practices, overcoming barriers to collaboration, managing difficult relationships with coworkers, and contributing purposively to the functionality of collaboration. Data were gathered using a postal survey. The sample consisted of 457 employees working in the health care, social welfare, and educational settings in Finnish municipalities. Overall, the results suggested that collaboration management is related to employees’ positive views of work and versatile skills. Good awareness of services, well agreed-upon collaboration practices, and wellfunctioning collaboration were associated with employees’ influence over their own work, social support being received from managers, a perception of leadership justice, employee collaboration skills, and employee retention. On the other hand, barriers to collaboration seemed to reduce employees’ influence over their own work, social support, perceptions of leadership justice, collaboration skills, and employee retention. The findings indicate the need for effective collaboration management in multidisciplinary environments between the health care, social welfare, and education sectors that provide services for children and families to achieve employees’ positive views of work and versatile skills.